Heritability of morphological and life history traits in a pelagic tunicate - Lobón, C.M. (2011)
Populations may adapt in response to selection pressures imposed by global environmental change. In marine zooplankton, measurements of the heritability of key life history characters, and thus the potential for evolution, are still rare. Here we demonstrate the feasibility of conducting controlled mating experiments with the dioecious appendicularian Oikopleura dioica to explore the narrow-sense heritability and genetic correlation among morphological and life history traits. At our standard laboratory conditions (15 ± 1°C, 100 μg C l-1), mature females were larger (1.213 ± 0.19 mm, mean ± SD) and lived longer (8.5 ± 2.18 d) than did males (1.115 ± 0.15 mm, 7.6 ± 2.07 d). The heritability (±SE) of morphological characters was low (trunk size, 0.37 ± 0.25; house size, 0.39 ± 0.23) to moderate (tail length, 0.50 ± 0.31). In contrast, an important life history trait, lifespan, showed high heritability (0.89 ± 0.47) and may therefore respond rapidly to selection pressure, either in the laboratory or in the wild. © Inter-Research 2011.